2012
DOI: 10.1007/s10886-012-0176-9
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated Cuticular Hydrocarbons Synergize Responses to Sex Attractant Pheromone in the Yellow Peach Moth, Conogethes punctiferalis

Abstract: Four trienyl hydrocarbons, (Z3, Z6, Z9)-tricosatriene (Z3, Z6, Z9-23:HC), (Z3, Z6, Z9)-pentacosatriene (Z3, Z6, Z9-25:HC), (Z3, Z6, Z9)-heptacosatriene (Z3, Z6, Z9-27:HC), and (Z3, Z6, Z9)-nonacosatriene (Z3, Z6, Z9-29:HC) were identified in a non-polar fraction of the body wax of male and female yellow peach moth, Conogethes punctiferalis. The relative amounts and ratios of these hydrocarbons differed between sexes. In females, the ratios in body wax and pheromone gland extracts were similar, with lesser amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 29 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…The yellow peach moth, Conogethes punctiferalis (Guenée), is widely distributed in tropical and eastern Asia and Australia, and causes damage to many orchard, spice, and vegetable crops [ 25 , 26 ]. Although C .…”
Section: Introductionmentioning
confidence: 99%
“…The yellow peach moth, Conogethes punctiferalis (Guenée), is widely distributed in tropical and eastern Asia and Australia, and causes damage to many orchard, spice, and vegetable crops [ 25 , 26 ]. Although C .…”
Section: Introductionmentioning
confidence: 99%
“…This is partly due to the difficulty in identifying behaviorally and physiologically active compounds when these have low or no volatility. To date, a partial analysis of the cuticular compounds was undertaken in eight moth species [Cydia pomonella (Piskorski et al, 2010), Conogethes punctiferalis (Xiao et al, 2012), Orgyia leucostigma (Grant et al, 1987), Lymantria dispar (Jurenka and Subchev, 2000), Helicoverpa zea, Heliothis virescens, Manduca sexta (Carlson and Milstrey, 1991;Böröczky et al, 2008), Anticarsia gemmatalis (Heath et al, 1983)] and in eight butterfly species [Colias eurytheme (Grula et al, 1980;Sappington and Taylor, 1990c), Idea leucone (Nishida et al, 1996;Schulz and Nishida, 1996), Pieris rapae (Arsene et al, 2002), Papilio polytes (Ômura and Honda, 2005), two species in the Danaus genus (Hay-Roe et al, 2007) and two species in the Lasiommata genus (Dapporto, 2007)]. It was shown that some of these compounds act as MSP (Sappington and Taylor, 1990c;Schulz and Nishida, 1996) or play a key role in reproductive isolation between closely related species (Grula et al, 1980), but the structure or the function of the large majority of the chemicals found on the cuticle of Lepidoptera remains so far uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…In C. punctiferalis, Xiao et al (2012) demonstrated that the addition of T23 enhanced the activity of the aldehyde pheromone blend (a mixture of E10-16:Ald and 11 Z10-16:Ald) by increasing the time spent close to the source as well as the number of source contacts. More crambids may have T23 in the pheromone gland and use it in combination with Type-I components as their sex pheromone components.…”
Section: Discussionmentioning
confidence: 99%
“…T23 and other type-II alkenes have recently been identified in the pheromone gland or body surface wax of five crambid species: Neoleucinodes elegantalis (Cabrera et al, 2001), Conogethes pluto (EI-sayed et al, 2013), Conogethes punctiferalis (Xiao et al, 2012), Deanolis sublimbalis (Gibb et al, 2007), and Omphisa anastomosalis (Yan et al, 2014). In C. punctiferalis, Xiao et al (2012) demonstrated that the addition of T23 enhanced the activity of the aldehyde pheromone blend (a mixture of E10-16:Ald and 11 Z10-16:Ald) by increasing the time spent close to the source as well as the number of source contacts.…”
Section: Discussionmentioning
confidence: 99%